2013
DOI: 10.1105/tpc.113.111658
|View full text |Cite
|
Sign up to set email alerts
|

Plant Immune Responses Against Viruses: How Does a Virus Cause Disease?

Abstract: Plants respond to pathogens using elaborate networks of genetic interactions. Recently, significant progress has been made in understanding RNA silencing and how viruses counter this apparently ubiquitous antiviral defense. In addition, plants also induce hypersensitive and systemic acquired resistance responses, which together limit the virus to infected cells and impart resistance to the noninfected tissues. Molecular processes such as the ubiquitin proteasome system and DNA methylation are also critical to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
277
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(284 citation statements)
references
References 176 publications
(280 reference statements)
2
277
1
4
Order By: Relevance
“…However, they have evolved ways to use a number of host factors including proteins, lipids, and metabolites to meet their demands and reprogram host cell metabolism for their robust replication. Successful infection also involves efficient counterdefense imposed by the host (21). To achieve this, plant viruses use a variety of strategies to suppress or circumvent host defense systems and promote their infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, they have evolved ways to use a number of host factors including proteins, lipids, and metabolites to meet their demands and reprogram host cell metabolism for their robust replication. Successful infection also involves efficient counterdefense imposed by the host (21). To achieve this, plant viruses use a variety of strategies to suppress or circumvent host defense systems and promote their infection.…”
mentioning
confidence: 99%
“…To achieve this, plant viruses use a variety of strategies to suppress or circumvent host defense systems and promote their infection. These include the formation of virusinduced miniorganelles like membranous structures to increase the local concentration of proviral factors and viral RNA template and to sequester newly synthesized viral genomes from host nucleases (22,23), the exploitation of viral suppressors of RNA silencing to block the degradation or translation repression of viral RNAs, and interference with the phytohormone signaling involved in antiviral defense (21). Despite a number of recent advances that unveil mechanisms underlying plant-virus molecular arms race (reviewed in refs.…”
mentioning
confidence: 99%
“…The molecular arms race between a virus and its host can be regarded as an analogous zigzag model (Mandadi and Scholthof, 2013;Nakahara and Masuta, 2014). Viral double-stranded RNAs (dsRNAs) produced during virus replication can be considered as virus-associated molecular patterns (Niehl et al, 2016) that induce antiviral RNA silencing (pattern-triggered immunity) against viruses.…”
mentioning
confidence: 99%
“…The different levels of resistance to CMV exhibited by the regenerants could reflect different levels of defensive reactions. Mandadi and Scholthof (2013) reported that during a viral infection, the Hypersensitive Response (HR) of the resistant plants would be initiated by Avr/Rprotein. The reaction induced metabolic changes which include levels of such phytohormones as Salicylic Acid (SA), Jasmonic Acid (JA) and Nitric Oxide (NO).…”
Section: Ajabsmentioning
confidence: 99%